Keselarasan pancasila dan konstitusi di indonesia: menatap masa depan demokrasi indonesia di era digital - Rimadhani, difah (Maliki Interdisciplinary Journal, 2026)
The development of digital technology has brought significant changes to Indonesia’s democratic system. The presence of social media and digital spaces opens opportunities for broader public participation in political life, but it also creates challenges such as the spread of hoaxes, political polarization, hate speech, and the decline of democratic ethics. This article aims to discuss the importance of aligning Pancasila and the Constitution in facing the future of Indonesian democracy in the digital era. The writing of this article uses a literature study method, drawing references from various journals and sources that examine democracy, Pancasila, and the Constitution. The study shows that Pancasila is very important as a moral foundation and national identity, while the 1945 Constitution of the Republic of Indonesia provides the legal basis to maintain an orderly and fair democracy. In addition, young people and political education play a key role in building a healthy and responsible digital democracy. Therefore, strengthening Pancasila values, constitutional awareness, and digital literacy are essential steps to protect the quality of Indonesia’s democracy in the middle of global technological change.